Albumin-Bilirubin Score: A Novel Mortality Predictor in Valvular Surgery - Zihni Mert Duman; Barış Timur (Brazilian Journal of Cardiovascular Surgery, 2022)
ABSTRACT Introduction: The heart and liver are two organs that are closely related. The Albumin-Bilirubin (ALBI) score is a developed scoring system for assessing liver function. The aims of this study were to examine the correlation between preoperative ALBI score and pulmonary artery pressure and to investigate its ability to predict heart valve surgery mortality outcomes. Methods: The data of 872 patients who underwent isolated and combined heart valve surgery from 2014 to 2021 were retrospectively screened. In the preoperative period, 152 patients with laboratory tests including albumin and total bilirubin were found and analyzed retrospectively. Thirteen of these patients were excluded from the study. The remaining 139 patients were included in the analysis. Baseline demographic data, echocardiography data, performance status, laboratory data, operative data, and postoperative status were collected. The optimal cutoff value of preoperative ALBI score was calculated. Results: The cutoff for ALBI scores was calculated as -2.44 to predict in-hospital mortality (sensitivity = 75.0%, specificity = 70%). Based on the cutoff value, 90 patients had a low ALBI score (≤ -2.44, 64.7%) and 49 patients had a high ALBI score (> -2.44, 35.3%). High ALBI score was associated with an increased incidence of acute kidney injury and in-hospital mortality, and a positive correlation was found between ALBI score and pulmonary artery pressure. Conclusion: In patients with valvular surgery, high ALBI score was an independent prognostic factor of in-hospital mortality and acute kidney injury. It is easily measurable and a cost-effective way to predict mortality.